Dissociative Social Interaction of Plasma Farmers and Palm Oil Companies in East Kotawaringin - Rinto Alexandro; Anyualatha Haridison; Orbit Thomas; Simpun Simpun; Fendy Hariatama (Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to analyze the forms of social interaction between plasma farmers and the Sarawak Damai Estate (SDE) Sawit Company in Pundu Village, Cempaga Hulu District, East Kotawaringin Regency. For the objectives to be answered, a qualitative approach was used to withdraw purposive sampling informants with data collected from oil palm farmers (primary) and documentation (secondary). The data collection techniques used are observation, interview, and documentation. The results showed that social interaction between the plasma farmers community and the SDE Company in Pundu Village, namely dissociative social interaction, occurred during the entry phase of the SDE Palm Oil Company and the management of the oil palm plantation. In this dissociative interaction, the plasma farmer community strengthens its solidarity in fighting against companies that are considered to be doing things that are detrimental to farmers. Therefore, social interaction between the plasma farmer community and the SDE Palm Oil Company in Pundu Village is dissociative.